The Role Of A Dignified Judge Within The Scope Of Judicial Power In Indonesia - Ibnususilo, Efendi; Suparto, Suparto; Akbar, Aryo; Taufiqurrahman, Faishal (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The supervisory function of the Judicial Commission at that time was met with a lot of resistance from judges, which eventually led to the submission of a judicial review of Law No. 22/2004 on the Judicial Commission to the Constitutional Court, which the Constitutional Court granted. With the granting of the judicial review petition, the Judicial Commission's supervisory function over judges ceased to exist. This raises the question of whether the judges will be able to carry out their duties fairly without external supervision. Purpose Study: Can these judges still carry out their duties fairly without external supervision? If so, then what is the role of these dignified judges within the scope of judicial power in Indonesia? This article uses normative legal research that analyzes relevant secondary data related to the role of dignified judges within the scope of judicial power. This research concludes that a dignified judge is a judge who works professionally based on ethical integrity, moral integrity and intellectual integrity. In order for this to be done, it is necessary to have supervision, both internally and externally. This research shows that there are still many judicial mafias in Indonesia, one of which comes from the judges themselves. this shows that there are still judges who do not work professionally by ignoring ethical and moral values so that many decisions are made that harm justice in society